Alemtuzumab in the treatment of multiple sclerosis: key clinical trial results and considerations for use. (January 2015) - Havrdova, Eva; Horakova, Dana; Kovarova, Ivana
Alemtuzumab is a humanized monoclonal antibody therapy that has recently been approved in over 30 countries for patients with active relapsing-remitting multiple sclerosis. It acts by targeting CD52, an antigen primarily expressed on T and B lymphocytes, resulting in their depletion and subsequent repopulation. The alemtuzumab clinical development program used an active comparator, subcutaneous interferon beta-1a, to show that alemtuzumab is a highly efficacious disease-modifying therapy, with benefits on relapses, disability outcomes, and freedom from clinical disease and magnetic resonance imaging activity. The safety profile was consistent across studies and no new safety signals have emerged during follow-up in the extension study. Infusion-associated reactions are common with alemtuzumab, but rarely serious. Infection incidence was elevated with alemtuzumab in clinical studies; most infections were mild or moderate in severity. Autoimmune adverse events occurred in approximately a third of patients, manifesting mainly as thyroid disorders, and less frequently as immune thrombocytopenia or nephropathy. A comprehensive monitoring program lasting at least 4 years after the last alemtuzumab dose allows early detection and effective management of autoimmune adverse events. Further experience with alemtuzumab in the clinic will provide needed long-term data.